Motivasi dan Partisipasi Petani dalam Pengelolaan Hutan Kemiri di Kabupaten Maros Provinsi Sulawesi Selatan - Adi Riyanto Suprayitno; Sumardjo Sumardjo; Darwis S Gani; Basita Ginting Sugihen (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2012)
The existence of candlenut forest in Maros District, today, is a successfull evidence of farmers living around the forest participation. Farmers around the candlenut forest has participated in managing that forest since 1826 to meet their subsitence need. They use the candlenut fruit to be one of their household income generating. Hence, those farmers have important roles to manage and to keep that forest sustainability. Any activity, including farmers participation, will undergo enthusiatic if there is any motivation within the person doing that activity. The research intended to identify and analize the contribution of farmers’ motivation to their participation in managing and utilizing candlenut forest. The data were collected on January-Maret 2010 in Maros District, South Sulawesi Province using some methods: questionnare list, interview, observation, and documents. The data were analyzed using (1) descriptive statistics, and (2) inferensial statistics based on SEM using LISREL 8.70 software programming. The result shows that farmers’ motivation is in the middle level, but their participation in managing and utilizing candlenut forest is categorized in low level. The Farmers’ motivation, however, has a positive contribution for increasing farmers participation in managing and utilizing candlenut forest.Keywords: Farmers’ motivation, farmers’ partisipation, candlenut forest